PENERAPAN MODEL PEMBELAJARAN BERDASARKAN MASALAH UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS V SDN 015 TERUSAN KEMPAS KECAMATAN GAUNG - Lenni Efridawati; Munjiatun Munjiatun; Mahmud Alpusari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem is undelined by the low of the result of mathematic study in mathematic learning. This is caused by the lack of the teacher’s knowledge toward mathematic learning concept, teacher is still using speech method in teaching and learning process. The students are rerely given opportunity in searching and improving of the thinking ability to build knowledge and experience of learning. To solve the problem, problem basic learning Model can improve the result of science study on the fifth grade students of SD Negeri 015 Terusan Kempas. The subject of the research is the fifth grade students of SD Negeri 015 Terusan Kempas of year academic of 2014/2015, with 12 students. This research used Class Action Research Method design which is done twice cycles. Each cycle is applied in twice with once of examination at the end of the cycle that aimed to improve the result of science learning of the fifth grade students of SD Negeri 015 Terusan Kempas. The result of result shows that the implied of the Problem Basic Learning Design can improve the science study of the fifth grade students of SD Negeri 015 Terusan Kempas. The basic score is 47,50 then on the cycle I it increases to 66,67 from the basic score, and increases to 76,67 then cycle I in cycle II. The explaination above can be cancluded that aplication of Problem Based Learning Model can improve the result of mathematic study of fifth grade of SD Negeri 015 Terusan Kempas.Key words: model Problem Based Learning, the result of mathematic study learning